RELEVANSI PERDA NOMOR 3 TAHUN 1991 DALAM PEMBANGUNAN PARIW ISATA BUDAYA BALI - Hadi Sukarno, Teguh (JURNAL KEPARIWISATAAN, 2007)
The Government of Bali decided that culture tourism concepts were viewedas the ideology, spirit, guidelines, framework and solutions in developing tourismin Bali. These decisions were then legitimized in a form of provincialrules "Perda no 3, tahun 1974" concerning the cultural tourism. The relationshipof tourism development and cultural development runs in harmony.It can be seen obviously that the Balinese awareness of their culture comessimultaneously as the tourism of Bali develops. The culture of Bali which isbased on Hindu Relegion is implemented as a fundamental base, dominantfactor and motor by which the tourism of Bali is developed.